PERAN MAQASHID SYARIAH DALAM MEWUJUDKAN KEADILAN NAFKAH SUAMI - Fauzi, Ahmad (MAQASHID Jurnal Hukum Islam, 2024)
In principle, households cannot be separated from the rights and obligations of their owners. The husband is obliged to support the family, while the wife has the obligation to manage the household as well as possible. This research uses a qualitative research methodology with a focus on field research studies, producing data through interviews that can be analyzed descriptively where the interviewees describe their own experiences as the main interview subjects, complemented by a collection of primary and secondary data. Next is a data collection technique that uses observation, questionnaires, and documentation with four subjects who are intrinsically motivated to research primary data. The findings of this research show that, according to Maqashid Al-Syari's perspective, human resources are a means of preventing poverty, promoting family harmony. , and protecting basic rights such as religion, family, family life, and the human heart is very important. As the main breadwinner, it is included in the maslahah daruriyah category. In terms of Islamic law, there is no prohibition on wives working to earn a living as long as it does not conflict with Islamic Sharia.